2021
DOI: 10.1111/hel.12847
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA NEAT1 promotes tumorigenesis in H. pylori gastric cancer by sponging miR‐30a to regulate COX‐2/BCL9 pathway

Abstract: Background: Helicobacter pylori (H. pylori) is a carcinogenic factor for gastric cancer. Our previous study demonstrated that H. pylori decreased the expression of microRNA(miRNA)-30a to promote the tumorigenesis in gastric cancer. However, the upstream regulatory mechanism of miR-30a hasn't wellelucidated. In this study, we found the long non-coding RNA (lncRNA) NEAT1 may sponge miR-30a to regulate COX-2/BCL9 pathway.Methods: The expression of NEAT1 was detected in gastric cancer tissues and tumour adjacent t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…Studies have shown that NEAT1 can upregulate the expression of ABCC4, JAG1, SOX11, COX-2, etc. These factors will finally promote the proliferation, migration, and invasion of gastric cancer [ 49 , 53 , 54 , 55 ].…”
Section: Neat1 Sponges Micrornas and Stabilizes Mrnasmentioning
confidence: 99%
“…Studies have shown that NEAT1 can upregulate the expression of ABCC4, JAG1, SOX11, COX-2, etc. These factors will finally promote the proliferation, migration, and invasion of gastric cancer [ 49 , 53 , 54 , 55 ].…”
Section: Neat1 Sponges Micrornas and Stabilizes Mrnasmentioning
confidence: 99%
“… 32 lncRNA NEAT1 may regulate the COX-2/BCL9 pathway by sponging miR-30a (miR-30a-3p and miR-30a-5p) and thus act as a promoter of tumorigenesis in H pylori GC. 33 Although H pylori infection is closely associated with the progression of GC, the mechanisms underlying this process are not fully understood. In this study, OTX2-AS1 expression was significantly negatively associated with H pylori infection in GC patients ( P = .006).…”
Section: Discussionmentioning
confidence: 99%
“…Literature search on “lncRNA-miRNA pairs” in cancer revealed one lncRNA (MALAT1) -miR125b interaction in laryngocarcinoma ( Zong et al, 2021 ), three lncRNA (TUG1, NEAT1, MALAT1) -miR-34a interactions reported in endometrial cancer, Nasopharyngeal Cancer, Melanoma ( Liu et al, 2017 ; Ji et al, 2019 ; Li et al, 2019 ) and three lncRNA (PVT1, NEAT1, and MALAT1) -miR-30a-5p interactions in papillary thyroid carcinoma, gastric cancer, Hepatocellular Carcinoma ( Feng et al, 2018 ; Pan et al, 2018 ; Rao et al, 2021 ). Previous studies revealed that the lncRNAs H19 and NEAT1 were found to directly target miR-193a-3p in Hepatocellular Carcinoma and Lung Adenocarcinoma, respectively ( Ma et al, 2018 ; Xiong et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%